Mountain View Cemetery, Capulin, New Mexico July 2006 - 20160731 frey50 (Raton, NM Lane Barraza, 2006)
This is a listing for the Mountain View Cemetary in Capuling, New Mexico.
The Mountain View Cemetery Records were updated in July, 2006 by Lane Barraza and Sandra Barazza
N.M. Cities and Towns - Capulin
Keywords: Sandra Barraza; Cemetery Records - Capulin, NM; New Mexico -- Capulin, New Mexico